Adequate supplemental irrigation amount during the critical period for yield in chia prevents reductions in radiation capture, radiation and water use efficiencies, and grain yield - Diez, Josefina (2024)
Chia is generally grown under rainfed conditions and is often under water deficit conditions during the critical period of flowering and grain filling when yield is determined. The objective of this study was to determine how intercepted photosynthetically active radiation (iPAR), radiation use efficiency (RUE), water use efficiency (WUE), and grain yield were affected by different soil water availabilities during the critical period for yield in chia. Four levels of total available water (TAW) during the critical period were obtained using supplemental drip irrigation including: T90 (90% TAW), T65 (65% TAW), T45 (45% TAW), and T30 (30% TAW). No reductions in iPAR and RUE (dry matter or yield per unit of intercepted radiation) were found between T65 and T90, which led to similar dry matter and grain yield. Water availabilities equal to or lower than 45% of TAW decreased iPAR, RUE, dry matter, and grain yield. The decrease in RUE under low TAW was associated with reductions in WUE (dry matter per mm of evapotranspiration) and in crop conductance (gc; evapotranspiration per unit of iPAR). These reductions in WUE and gc occurred, respectively, due to the greater contribution of soil evaporation to crop evapotranspiration and less transpiration per unit of intercepted radiation when TAW was 45% or lower. The use of supplemental irrigation to ensure 65% of TAW in the soil during the critical period for yield would reduce the importance of soil evaporation and increase crop transpiration by increasing crop ground cover and would lead to improved grain yields in chia.